OPTIMIZATION OF PROCESS PARAMETERS FOR THE MACHINING OF INCOLOY 800HT ON EDM (International Journal of Engineering Sciences & Management Research, 2017)
Electrical discharge machining (EDM) have Non-traditional machining processes work on the basis of thermo electric energy between the work piece and the electrode. This type of process, material removal by series of successive discrete electric discharges between electrode and the work piece .The performance of EDM process using different type of electrode material. The Material Removal Rate (MRR), Tool Wear Rate (TWR) and Surface Roughness (SR) are measures for detailed analysis by use of different electrode materials Brass, Copper and Copper Tungsten and work piece material as INCOLOY800HT have employed for the experiments. The dielectric fluid used as EDM Dielectric fluid. Objective of this project is show the best material in terms of higher MRR, lower TWR, and excellent surface finish